The Arf-GEF GBF1 undergoes multi-domain structural shifts to activate Arf at the Golgi - Meissner, Justyna M.; Akhmetova, Katarina; Szul, Tomasz; Viktorova, Ekaterina G.; Sha, Bingdong; Bhatt, Jay M.; Lee, Eunjoo J.; Kahn, Richard A.; Belov, George A.; Chesnokov, Igor; Sztul, Elizabeth (Frontiers in Cell and Developmental Biology, 2023)
Golgi homeostasis require the activation of Arf GTPases by the guanine-nucleotide exchange factor GBF1, whose recruitment to the Golgi represents a rate limiting step in the process. GBF1 contains a conserved, catalytic, Sec7 domain (Sec7d) and five additional (DCB, HUS, HDS1-3) domains. Herein, we identify the HDS3 domain as essential for GBF1 membrane association in mammalian cells and document the critical role of HDS3 during the development of D. melanogaster.We show that upon binding to Golgi membranes, GBF1 undergoes conformational changes in regions bracketing the catalytic Sec7d. We illuminate GBF1 interdomain arrangements by negative staining electron microscopy of full-length human GBF1 to show that GBF1 forms an anti-parallel dimer held together by the paired central DCB-HUS core, with two sets of HDS1-3 arms extending outward in opposite directions. The catalytic Sec7d protrudes from the central core as a largely independent domain, but is closely opposed to a previously unassigned α-helix from the HDS1 domain. Based on our data, we propose models of GBF1 engagement on the membrane to provide a paradigm for understanding GBF1-mediated Arf activation required for cellular and organismal function.